Mitochondrial neurogastrointestinal encephalomyopathy: Case report - Yaşar ÇOLAK,; İlyas TUNCER,; Erkan Çağlar,; Dilek BARUTÇU,; Celal ULAŞOĞLU,; Şafak KIZILTAŞ, (Turkish Journal of Gastroenterology, 2019)
-